Seizing the Opportunity: Creating a Chair Development Network - Margaret A Thomas-Evans; Natalia Rybas; Carrie Longley (Academic Chairpersons Conference Proceedings, 2016)
In this presentation, we discuss an example of developing a leadership network for Chairs on a small regional campus. We argue that when a campus has limited leadership capital, a peer group can serve as powerful professional development platform for new and upcoming chairs.
Keywords: leadership; professional development; peer support; chair network